Durability, Service Life, and Techno-Economic Analysis of Non-Proprietary UHPC - Bijaya Rai; Kay Wille (Fibers)
Non-proprietary ultra-high-performance concrete (UHPC) has been developed by numerous research institutes, each exhibiting unique characteristics distinct from both commercial and other non-proprietary UHPC formulations. However, comprehensive techno-economic analyses (TEA) comparing UHPC to conventional concrete, alongside extensive long-term durability assessments, remain limited. This study bridges these gaps by evaluating the long-term durability, modeling service life, and conducting a TEA of resource-efficient non-proprietary UHPCs. Durability characterization was conducted in accordance with ASTM standards, focusing on chloride ion penetration (via electrical surface resistivity), drying shrinkage, freeze–thaw (F–T) resistance, and absorption. These properties were monitored over a year to capture both transient and steady-state performance. A durability assessment factor (κ) was introduced to assess and compare the new UHPCs with existing alternatives. Results demonstrated that the UHPCs achieved high electrical surface resistivity, exceeding the low chloride ion penetration threshold of 21 kΩ∙cm within 1 week of casting. No deterioration was observed after 600 F–T cycles, indicating superior F–T resistance. Drying shrinkage remained below 0.1%, and absorption remained below 1.4%. These results highlight the long-term durability of the UHPCs, with a projected design service life surpassing 350 years, aligning closely with proprietary UHPC products.